2016
DOI: 10.11648/j.ijmi.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Size of Sella Turcica Among Adult Nigerians Resident in Lagos

Abstract: Abstract:One of the clinical significance of the sella turcica is the empty sella syndrome which is the condition of a shrunken or flattened pituitary gland; hence a familiarity with the sella turcica anatomy and radiological appearance is of great importance. The present study investigated the normal dimensions of the sella turcica and the relationship with gender and age in adult Nigerians resident in Lagos, using computed tomographs of patients who underwent CT head examination. This was carried out to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…On the other hand, in contrast to our findings and to the above-mentioned studies that reported sexual dimorphism of Sella Turcica; in Iraqi population (Hasan et al, 2016b), in Nigerian population (Olubunmi et al, 2016;Ejike et al, 2017), in Bangladeshi population (Islam at al., 2017), in Indian populations (Shaha et al, 2017), and in Turkish population (Taner et al, 2019); reported absence of sex related difference in Sella measurements.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in contrast to our findings and to the above-mentioned studies that reported sexual dimorphism of Sella Turcica; in Iraqi population (Hasan et al, 2016b), in Nigerian population (Olubunmi et al, 2016;Ejike et al, 2017), in Bangladeshi population (Islam at al., 2017), in Indian populations (Shaha et al, 2017), and in Turkish population (Taner et al, 2019); reported absence of sex related difference in Sella measurements.…”
Section: Discussioncontrasting
confidence: 99%
“…Sexual dimorphism of Sella Turcica measurements is still a point of controverse among different populations (Olubunmi et al, 2016;Islam at al., 2017;Turamanlar et al, 2017;Chou et al, 2021). The aim of the present study was to evaluate the sex related differences in the metric measures of Sella Turcica and its boundaries of clinoid processes among a sample of adult Egyptian population; in line with establishing sex determination statistical models specific for Egyptian population.…”
Section: Discussionmentioning
confidence: 99%
“…Of the articles included, six performed correlations with the skeletal class [ 5 , 9 , 17 , 22 , 26 , 28 ] ( Table 1 ). Regarding the type of examination, seven articles used lateral view radiographs [ 5 , 8 , 16 , 20 , 22 , 26 , 28 ]; and nine CT scans [ 9 , 11 , 12 , 17 , 21 , 25 , 27 , 29 , 30 ], five of which were CBCTs [ 9 , 12 , 17 , 27 , 29 ]. Most studies digitally analyzed the images [ 8 , 9 , 11 , 12 , 17 , 20 , 21 , 25 , 29 , 30 ] ( n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…Several investigations have been carried out with non-syndromic individuals in different populations aiming at evaluating the morphology and parameters of normality of the ST [ 4–31 ]. For this purpose, cephalometric radiographs (CR) [ 4–8 , 16 , 18–20 , 22–24 , 26 , 27 ], as well as multislice computed tomography (MSCT) [ 10 , 11 , 13–15 , 21 , 25 , 30 ] and cone beam computed tomography (CBCT) images have been employed [ 9 , 12 , 17 , 27 , 29 , 31 ]. Local and regional validation of these methods are of great relevance because of possible variations in different populations, and some studies have already found significant differences in ST morphology among different ethnic groups [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sathyanarayana et al [9] found no significant correlation between the ST depth and diameter with gender, but the ST length was significantly greater in males than females. Also, Yan et al [31], Shrestha et al [33], Islam et al [42], Olubunmi et al [43], Valizadeh et al [34], and Nagaraj et al [44] found no significant correlation between the ST dimensions and gender. Hasan et al [45] indicated no significant difference between males and females in ST dimensions, except in ST depth.…”
Section: Discussionmentioning
confidence: 98%